Islamic Monetary Instruments and Central Bank Policy: A Systematic Literature Review on Effectiveness, Transmission Channels, and Macroeconomic Outcomes - Muslim Marpaung; Irma Suryani Lubis (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2026)
The rapid development of Islamic finance has encouraged central banks in dual banking systems to design monetary instruments that comply with Sharia principles while maintaining macroeconomic stability. However, the effectiveness of Islamic monetary instruments and their transmission mechanisms remain widely debated in the literature. This study aims to systematically review the empirical and conceptual literature on Islamic monetary instruments, focusing on their effectiveness, transmission channels, and macroeconomic outcomes. Using a Systematic Literature Review (SLR) approach guided by the PRISMA framework, this research synthesizes findings from major studies examining Islamic monetary policy operations, banking transmission mechanisms, and their impacts on inflation, output, and financial stability. The results reveal that the financing/credit channel and the interest–profit pass-through mechanism are the dominant transmission pathways in dual banking systems. Although Islamic banks often demonstrate relative stability during monetary shocks, policy transmission remains partly influenced by conventional interest rate benchmarks due to institutional and market structure factors. The effectiveness of Islamic monetary instruments is largely determined by the depth of Islamic money markets, the availability of liquid instruments such as central bank sukuk, and the strength of regulatory and institutional infrastructure. Furthermore, empirical evidence linking Islamic monetary instruments directly to macroeconomic outcomes such as inflation and growth remains limited. This study proposes an integrated conceptual framework linking Islamic monetary instruments, transmission channels, and macroeconomic outcomes, moderated by institutional quality, market share of Islamic banking, and market depth. The findings contribute to the literature by providing a comprehensive synthesis of existing research and offering policy insights for strengthening Islamic monetary policy frameworks in dual financial systems.